Assessment of immunization coverage in district Srinagar of Kashmir - Ashraf, Ambrine; Samreen, Sheema; Khan, S. M. Salim; Haq, Inaamul; Amin, Mariya (International Journal Of Community Medicine And Public Health, 2019)
Background: Immunization is till now most safe, cost effective and powerful intervention that has decreased the burden of vaccine preventable infectious diseases all over the world. The aim of this study was to estimate the immunization coverage among children aged 12-23 months in district Srinagar of Jammu and Kashmir. Methods: The study sample included 30 clusters from district Srinagar selected as per the 30×7 cluster sampling method. Results: It was found that fully immunized children were 87.14% and 12.26% of children were partially immunized and none was unimmunized. Regarding the individual vaccine coverage, it was highest for OPV1 (99.52%) followed by BCG and OPV0 (99.05%) and lowest for Hepatitis birth dose (95.24%). The dropout was found highest (6.22%) for OPV1-OPV3 and lowest (1.47%) for LPV1 - measles/MCV (1.47%). Conclusions: The immunization of district Srinagar is above 85% and this gives a positive hope for better future to reach coverage of 100%.